Analisis Beban Kerja Perawat Berdasarkan Tingkat Ketergantungan Pasien di Rumah Sakit Soerojo Magelang - Urwatul Usqo; Muadi Muadi; Dewi Erna Marisa (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Nurses’ workload is one of the factors that influence the quality of nursing care and patient safety. The level of patient dependency is a key factor determining the magnitude of nurses’ workload because it relates to the time, energy, and attention required to provide nursing care. Objective: To analyze nurses’ workload based on the level of patient dependency in Ward Lily 1 at Soerojo Hospital in Magelang. Methods: A descriptive quantitative design with a cross-sectional approach. The study sample consisted of 21 nurses selected using total sampling. Data were collected using a nurse workload questionnaire and the Douglas method’s patient dependency level classification form, then analyzed using the chi-square test. The results showed that the majority of nurses experienced heavy workloads (14 nurses, 67%), while 5 nurses (24%) experienced moderate workloads. Result: Patient dependency levels were dominated by the partial care category (12 patients, 57%), followed by minimal care (4 patients, 19%) and total care (5 patients, 24%). The chi-square analysis yielded a significant p-value of 0.001 < α = 0.005. Implication: It was concluded that there is a relationship between patient care levels and workload.